ALADDIN study: does assisted hatching of vitrified/warmed blastocysts improve live birth rate? Protocol for a multicentric randomised controlled trial. Issue 7 (19th July 2020) - Alteri, Alessandra; Guarneri, Cristina; Corti, Laura; Restelli, Liliana; Reschini, Marco; Giardina, Paolo; Papaleo, Enrico; Somigliana, Edgardo; Viganò, Paola; Paffoni, Alessio
Abstract : Introduction: Recent data suggest a higher clinical pregnancy rate performing assisted hatching (AH) on previously cryopreserved embryos but fail to demonstrate significant effects on live birth rate. However, current evidence is based on studies with a small sample size and may hide a type II error. Moreover, poor attention has been given to the specific effect of AH on frozen/thawed blastocysts. To shed light on this topic, we developed the present protocol for a randomised trial to investigate the benefits of the laser-mediated partial removal of the zona pellucida in vitrified/warmed blastocysts. Methods and analysis: The pArtiaL zonA pelluciDa removal by assisteD hatchINg of blastocysts (ALADDIN) study is a multicentric prospective comparative study with a parallel randomised controlled design aiming to investigate whether AH performed on warmed blastocysts before embryo transfer can improve live birth rate. Women allocated to the control group will undergo embryo transfer of blastocysts not previously subjected to AH. Two infertility units will be involved in the study. Enrolment of patients will last 18 months with quarterly monitoring and the entire study is foreseen to be closed in 36 months. Secondary outcomes include: proportion of transferred blastocysts/thawed blastocyst, morphological features of blastocysts before embryo transfer, implantation, biochemical pregnancy, clinical pregnancy (ultrasound visible gestational sac), miscarriage, multiple pregnancy, preterm birth (<37 weeks of gestation), obstetrical and neonatal complications and congenital anomaly rates. Ethics and dissemination: This protocol received a favourable ethical opinion from the Ethical Committee of IRCCS San Raffaele Scientific Institute and the Ethical Committee Area 2 Milan. Each participant will provide written consent to participate and remain encoded during the study. The trial results will be published in peer-reviewed journals and presented at conferences. Trial registration number: NCT03623659; Pre-results .